2013
DOI: 10.1038/ja.2013.53
|View full text |Cite
|
Sign up to set email alerts
|

Langkocyclines: novel angucycline antibiotics from Streptomyces sp. Acta 3034

Abstract: Langkocyclines A1-A3 and B1 and B2, five new angucycline antibiotics produced by Streptomyces sp. Acta 3034, were detected in the course of our HPLC-diode array screening. The producing strain was isolated from the rhizospheric soil of a Clitorea sp. collected from Burau Bay, Langkawi, Malaysia, and was characterized by morphological, physiological and chemotaxonomic features in addition to 16S ribosomal RNA gene sequence information. Strain Acta 3034 is closely related to Streptomyces psammoticus NBRC 13971(T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The potencies for 15 and 16 against the five cell lines tested in this study were similar to other cancer cell lines reported previously. 22, 26, 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potencies for 15 and 16 against the five cell lines tested in this study were similar to other cancer cell lines reported previously. 22, 26, 27 …”
Section: Resultsmentioning
confidence: 99%
“…As summarized in Table 5, both 15 and 16 showed moderate activity against S. aureus ATCC 25923, B. subtilis ATCC 23857, and M. smegmatis ATCC 607, with the minimum inhibitory concentration (MIC) values ranging from 8.1 to 25 µg/mL, which were similar to the reported MIC values for 15 and 16 against other S. aureus or B. subtilis species. 26, 27, 3234 Compound 5 showed weak activity against B. subtilis ATCC 23857 and M. smegmatis ATCC 607. As previously observed for known angucyclines and angucyclinones, 2 1–16 showed no activity against the Gram-negative E. coli ATCC 25922 and JM109 species.…”
Section: Resultsmentioning
confidence: 99%
“…Streptomyces sp. Acta 3034 from the rhizospheric soil of Clitorea sp., produced five new angucycline antibiotics, langkocyclines A1-A3, B1 and B2, which exhibited biological activities against Gram-positive bacteria and moderate inhibitory activities against several human tumor cell lines [10]. Streptomycetes may also promote the growth of the plant hosts by producing auxins that improve the root growth [11].…”
Section: Introductionmentioning
confidence: 99%
“…These moieties are linked to various aglycons as well as to other 2‐deoxyglycosides with divergence in sequence and stereochemistry. For example, repeating patterns (such as those found in langkocycline congeners) are reported, and heterogeneous patterns (such as that found in landomycin Y) are also known . Due to this diverse nature, oligosaccharides containing 2,3,6‐trideoxypyranoglycosides have been considered attractive synthetic targets .…”
Section: Figurementioning
confidence: 99%